2017
DOI: 10.3329/jbau.v15i2.35078
|View full text |Cite
|
Sign up to set email alerts
|

An economic analysis of Jara and Colombo lemon production in Bangladesh

Abstract: The study was conducted in two districts namely Sylhet and Narsingdi to investigate the production technology of Jara and Colombo lemon growers, estimate profitability and identify the constraints of Jara and Colombo lemon. A total sample of 120 farmers taking 60 for Jara lemon from Sylhet and 60 for Colombo lemon from Narsingdi was selected randomly for the study. Data were collected through face to face interview method by using structured questionnaire during April-May, 2016. Cost return analysis revealed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…The overall cost relating to acid lime was calculated by aggregating the cost incurred for labor, organic manure, and Bordeaux components along with micronutrients, plant protection, and other management costs. From the study, the majority of the production's expenses were contributed by labor costs excluding the land rent which was found similar to the previous reports of Kaysar et al (2017) in which the cost of labor accounted for around 67% of the cost of production of acid lime including land revenue, labor cost contribute 12.5% and land rent contribute 20.3% which was highest among other cost in Palpa district. Thus, indicating that the production of acid lime was very labor-intensive and land occupying.…”
Section: Cost Of Acid Lime Productionsupporting
confidence: 87%
“…The overall cost relating to acid lime was calculated by aggregating the cost incurred for labor, organic manure, and Bordeaux components along with micronutrients, plant protection, and other management costs. From the study, the majority of the production's expenses were contributed by labor costs excluding the land rent which was found similar to the previous reports of Kaysar et al (2017) in which the cost of labor accounted for around 67% of the cost of production of acid lime including land revenue, labor cost contribute 12.5% and land rent contribute 20.3% which was highest among other cost in Palpa district. Thus, indicating that the production of acid lime was very labor-intensive and land occupying.…”
Section: Cost Of Acid Lime Productionsupporting
confidence: 87%
“…Sikha et al (2021), reported that Assam lemon is one of the most prominent commercial citrus fruits and productivity average had increased from 4421kg/ha to 7614kh/ha with 3.4:1 benefit cost ratio. Kaysar et al (2017), worked on the production of the Colombo and Jara lemons at Bangladesh, the highest gross return was found in 5 th years old lemon orchards followed by 11 th to 15 th year old lemon plants. Bukero and Philipos (2018), analysis the benefit cost ratio of Verbena (Lominat) lemons and proved this variety of herbal plants provides the net present value and benefit cost-ratio of 12828.5$/ha, 10043.6 and 0.2 at fresh bio-mass price of 0.4$/kg.…”
Section: Benefit-cost Ratio Of Lemon Orchards and Fruits From Five Ta...mentioning
confidence: 98%
“…Colombo lemon consumed directly as fresh fruit or the extracted juice is used for pickles and beverage production (Kaysar et al, 2017). Popular lemon squash is also prepared with the combination of colombo lemon and other citrus fruits.…”
Section: Introductionmentioning
confidence: 99%
“…Though Colombo lemon has been cultivated for many years at Narsingdi district of Bangladesh, only one variety which is suggestive achievement has been made in varietal improvement (Hoque et al, 2017;Kaysar et al, 2017). In homestead and kitchen garden this species could also be grown very easily.…”
Section: Introductionmentioning
confidence: 99%